Compaction of quartz-kaolinite mixtures: The influence of the pore fluid composition on the development of their microstructure and elastic anisotropy. (December 2016) - Beloborodov, Roman; Pervukhina, Marina; Luzin, Vladimir; Delle Piane, Claudio; Clennell, Michael B.; Zandi, Setayesh; Lebedev, Maxim
Abstract: Shales play important roles in sedimentary basins, acting as both seals and reservoir rocks, and knowledge of their anisotropic velocity trends is of practical importance for correct seismic image processing and inversion, and for seismic to well tie. Whereas velocity-depth trends are extensively studied for conventional reservoirs and critical factors that control their compaction are well understood, little work has been done on shales. Compaction trends of shaly formations are controlled by a number of parameters such as clay mineralogy, silt fraction and depositional environment. This large number of parameters, which are difficult if not impossible to control in naturally deposited shales, make the study of shale compaction a statistically complex, multivariate and non-unique problem. In such a situation, laboratory experiments that allow precise planning of mixture mineralogy and chemical compositions of pore fluids as well as an accurate control of microstructural changes seems to be an attractive alternative. In this work, we have conducted two sets of compaction experiments on quartz-kaolinite mixtures with 100%, 75% and 60% of kaolinite powders (dry weight). In the first set, the use of a KCl brine solution to saturate the mixtures has led to the aggregation of the existing clay particles with each other and with silt particles. In the other set, the mixtures have been treated with a dispersant to separate existing clay aggregates into individual platelets. The mixtures have been further compacted in an oedometric cell at uniaxial stresses up to 30 MPa. Compressional (in vertical and horizontal directions) and shear (in vertical direction) ultrasonic wave velocities have been measured during these compaction experiments and the P-wave anisotropy has been estimated. The effect of the chemical composition of the pore fluid on shale microstructure has been studied using the micro-CT and SEM image analysis. Neutron diffraction experiments have been conducted to understand the orientation of clay platelets at the final stage of the compaction. Our research shows that the chemical composition of pore fluid significantly affects the microstructure of the clay component and via this the elastic properties of the artificial shales. The samples with the dispersed clay microstructure (DCM) have shown larger elastic anisotropies at the same porosity and significantly larger anisotropies at the same stress. The dispersed clay platelets have orientated preferably parallel to bedding plane while the clay platelets in the samples with the aggregated clay microstructure (ACM) show a wider angle distribution in the absence of quartz particles (100% kaolinite samples). In the case of 40% of quartz fraction though, the clay particles are more aligned in the ACM sample than in the DCM one. Highlights: Pore fluid determines whether clay consists of dispersed or aggregated particles. Compaction trends and anisotropy of shales are shaped by this clay matrix. Dispersed clays are more aligned at low while aggregated at high silt fraction. Silt is more aligned in horizontal plane in aggregated shale at high concentrations. Dispersed shales show twice higher P-wave anisotropy at the same stress.